Role of TSH and O-GTT screening in pregnancy induced hypertension - Verma, Aruna; Kashyap, Monika; Gupta, Abhilasha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Objective of current study was to evaluate the prevalence of hypothyroidism and gestational diabetes in PIH patients and its impact on maternal and foetal outcome. Methods: A case-control study of 200 antenatal women; group A - PIH, 100 and group B normotensive - 100 women was carried out. Serum TSH and O-GTT screening was done in both groups. Results: In group A, 59% women had mild preeclampsia, 41% women had severe preeclampsia. Significantly raised TSH titre (>3 mIU/ml) was found in 36% women in group A and 9% women in group B (P value <0.0001). GDM was found in 33% women in group A and 8% women in group B (P value 0.0033). Conclusions: Incidence of both hypothyroidism (subclinical and clinical) and gestational diabetes is significantly high in women with PIH.